Developing Comic Learning Media With Nuances Of Student Learning Motivation In Thematic Learning In Madrasah Ibtidaiyah - Kurnia Dewi, Yeni (ATTA`DIB, 2025)
This study aims to determine effectiveness of comic media in class III thematic learning at MI Nurur Rahman Jember. This study uses research and development (Research and Development) which refers to the ADDIE development model which consists of 5 stages: analysis, design, development, implementation and evaluation. Data collection techniques using observation, interviews, questionnaires, tests and documentation. The results of the study show that: 1) The creation of comic media that has been tested for feasibility by obtaining validation results from media, material and language experts. which has been declared very feasible to use with a score of 91.2% from media experts, material experts get a score of 90%, and linguists get a score of 92%. 2) The effectiveness of comic media is obtained from the results of the pretest and posttest, the results of the pretest show a score of 45% and the results of the post-test show a score of 86% and the results of the calculation of the N-gain Score to determine whether comic media is effective or not, comic media obtains an average score - an average of 73% so that comic media is effectively used in thematic learning.